Prevalence of sub-clinical mastitis in dairy farms (Bangladesh Veterinarian, 2014)
A total of 560 lactating cows belonging to Bangladesh Agricultural University dairy farm (n = 59): Local Zebu (L), Local × Friesian (L × F), Local × Jersey (L × J), Local × Red Chittagong Cattle (L × RCC), Local × Sahiwal (L × SL), Red Chittagong Cattle (RCC); and Central Cattle Breeding Station and Dairy Farm (n = 501): Local Zebu, L × F, SL × F, Sahiwal and Australian Friesian Sahiwal (AFS) were selected to measure prevalence of subclinical mastitis (SM). The California Mastitis Test was done and the prevalence of SM was 68% on cow basis and 57% on quarter basis. The prevalence rate was significantly higher in L × F (87%, P < 0.05), SL × F (88%, P < 0.05), L × J (100%, P < 0.01), AFS (89%, P< 0.05) and SL (100%, P < 0.01). The local Zebu (31%) and RCC (28%) were least susceptible to SM. SM was significantly higher in multiparous (P < 0.05) and older cows (P < 0.05). The front quarters were more prone to SM than the rear. Factors such as breed, age, parity and management may have been responsible for high prevalence of SM in both farms. DOI: http://dx.doi.org/10.3329/bvet.v30i2.18257 Bangl. vet. 2013. Vol. 30, No. 2, 70-77